2009
DOI: 10.1017/s0317167100008179
|View full text |Cite
|
Sign up to set email alerts
|

Cine Phase-Contrast MR Images Failed to Predict Clinical Outcome Following ETV

Abstract: Endoscopic third ventriculostomy (ETV) has been a popular surgical option for obstructive hydrocephalus (OHCP) in recent decades. [1][2][3] A number of studies worldwide have reported favorable outcomes; 4-6 however, in some cases, ETV fails to resolve symptoms, even when it is technically successful with adequate patent stoma and fenestrated Lillequist membrane. [7][8][9][10][11] It has been hypothesized that patients might suffer from hydrocephalus caused by other obstructive membranes or by fibrosis in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 25 publications
0
5
1
Order By: Relevance
“…Although some patients may show adequate qualitative and quantitative data of flow through the ventriculostomy above the cutoff values, they display symptoms and signs of clinical deterioration and this is explained as inefficient ETV due to basal cisterns obstruction and considered communicating hydrocephalus which was observed by Di et al [18] , which was not reported in our study.…”
Section: Discussioncontrasting
confidence: 61%
“…Although some patients may show adequate qualitative and quantitative data of flow through the ventriculostomy above the cutoff values, they display symptoms and signs of clinical deterioration and this is explained as inefficient ETV due to basal cisterns obstruction and considered communicating hydrocephalus which was observed by Di et al [18] , which was not reported in our study.…”
Section: Discussioncontrasting
confidence: 61%
“…One study, in which most patients had elevated aqueductal stroke volume, showed only a small, non-significant decrease in flow pulsatility after ETV [184]. A more recent study found no association between ETV success and CSF flow pulsatility in the basal cisterns or at the cervicomedullary junction [185]. Thus, at present there is no obvious connection between CSF pulsatility and the success of ETV surgery.…”
Section: The Intracranial Pulse Wave - Clinical Studiesmentioning
confidence: 99%
“…This indicates that the distal CSF pathways beyond the basal cisterns, around the brain stem and cervicomedullary junction, may play an essential role in achieving ETV success in addition to an adequate fenestration. [61] Surgical Technique ETV is performed in supine position with head flexed so that the burr hole site is at the highest point. This also avoids over drainage of CSF and an entry of air in the ventricles and subdural space, especially in large ventriculomegaly.…”
Section: Pre-operative Imaging and Patient Selectionmentioning
confidence: 99%